Política pública e Compensação Ambiental no Brasil: o caso da Usina Hidrelétrica de Santo Antônio do Jari na Amazônia - Rafael Oliveira Fonseca (Confins)
Environmental issues should not be understood as a simple result of the relationships between human beings and nature but should be seen as part of a component of human relations, as an economic, political and cultural object. One of the instruments of public policy that is directly inserted in the complex and dynamic contemporary issues is the Environmental Compensation (EC). The objective of this paper is to analyze the implementation of the EC based on their legislation as well as a case study, in order to highlight its potential, as an instrument of public policy, in influencing the spatial planning, particularly from an environmental perspective, in a scenario that is involved by the interests and powers of various actors. Thus, in the first moment, an approach is presented about some key concepts of this analysis, as well about what is the EC and how its operationalization and calculation occurs. In a second moment, its application is analyzed based on a case study, the Santo Antônio do Jari Hydroelectric Power Plant located in the Amazon rainforest. Finally, some conclusions on the application of the instrument are presented and some possibilities for the future of this instrument in Brazil.